2016
DOI: 10.24059/olj.v20i3.691
|View full text |Cite
|
Sign up to set email alerts
|

Desired and Experienced Levels of Connectivity to an Asynchronous, Online, Distance Degree Program

Abstract: This study examined graduate students’ desired and experienced levels of connectivity in an online, asynchronous distance degree program. Graduate students enrolled in the Masters of Science in Special Education distance degree program at a Midwest university were surveyed on both desired and experienced connectivity to their program, students, instructors, and advisors. Overall, student’s desired and experienced high connectivity to the program, their advisors, and their instructors; experiencing and wanting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 21 publications
0
28
0
Order By: Relevance
“…Participants desired quality interaction with their tutors and advisors (Schroeder et al, 2016) and perceived them as primary sources of academic support (Cain et al, 2007). They perceived that providing feedback is the most important characteristic of a good DE tutor (Cain at al., 2007;Edwards et al, 2011;Howland & Moore, 2002;Lessing & Schulze, 2002) and expected quality and individualised feedback.…”
Section: Interactionmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants desired quality interaction with their tutors and advisors (Schroeder et al, 2016) and perceived them as primary sources of academic support (Cain et al, 2007). They perceived that providing feedback is the most important characteristic of a good DE tutor (Cain at al., 2007;Edwards et al, 2011;Howland & Moore, 2002;Lessing & Schulze, 2002) and expected quality and individualised feedback.…”
Section: Interactionmentioning
confidence: 99%
“…Students had negative attitudes toward inadequate online discussion durations (Risner & Kumar, 2016). While they expected advisors to promote peer interaction (Lessing & Schulze, 2002), their need to communicate with tutors and advisors was higher than their desire to connect with other students (Schroeder et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…There is agreement in literature that sending regular announcements or email reminders is an important engagement strategy (Martin and Bolliger 2018) and continuous prompting throughout a module will lead to improvements in self-regulation, learning and retention (Wandler and Imbriale 2017). However, not all students desire connection with the instructor or other learners and some might not respond to any engagement activities (Schroeder et al 2016). Where student numbers are small, educators can get to know their students and will therefore sense when to prod and remind and when to pull back.…”
Section: Discussion: Implications Limitations and Future Researchmentioning
confidence: 99%
“…Additionally, adequate enlightenment on why the respondents should consider it useful for partaking in the study should equally be given much attention. Schroeder, Baker, Terras, Mahar and Chiasson (2016) also demonstrated that approachability for immediacy effect towards communication satisfaction on asynchronous mediated communication can be enriched by increasing social presence via the degree of connectivity among the interacting entities. Though this was realized via a quantitative study conducted among teachers and distant masters' degree learners, the numbers of the respondents who willingly participated in the study seemed inadequate to generalize the outcome.…”
Section: What Are the Effects Of Approachability On Immediacy Towards Communication Satisfaction On Asynchronous Computer Mediated Communmentioning
confidence: 94%